Stereochemical reassignment of Mehta and Kundu's spiculoic acid a analogue. - Kirkham, J; Lee, V; Baldwin, J (2006)
A close examination of Mehta and Kundu's synthesis of an analogue of spiculoic acid A revealed discrepancies between their proposed structure and corresponding data. A revised structure is proposed for Mehta and Kundu's analogue after a careful analysis of their key synthetic transformations and published data. [reaction: see text].